Dental Implant Treatment At A Nigerian Teaching Hospital (2014)
Background: There has been an increase in the awareness of dental implant as a replacement option for missing teeth and this has consequently led to an increased demand for dental implant. Aim & Objective: To determine the distribution and pattern of implant placement in a tertiary hospital in a developing country. Materials and Methods: This retrospective study was conducted at the University College Hospital to assess the treatment outcome of all the patients who had had osseointegrated root form endosseous dental implants over a period of five years. The data obtained included age, gender, socioeconomic status (SES), medical history, reason for implant placement, number of implants per patient, distribution of missing teeth, complications and treatment outcome. The data were analyzed for percentages, means, SD and presented in tables and figures. Results: Forty two implants (40 conventional & 2 immediate) were placed in the 23 patients (M-15, F=8).There were 15(65.2%) males and 8(34.8%) females. Pre-implant placement ridge augmentation was done in 3(7.1%) patients while 9 (39.1%) patients had augmentation during implant placement surgery. Left maxillary central incisor was the most commonly replaced tooth in 31% followed by the right maxillary central incisor in 19%. The success rates in the study at 1 year and 5 years were 97.4% and 95.2% respectively. Conclusion: A high success rate (95.2%) of implant therapy at 5 years recorded in this study compared favorably with what is obtainable in many other countries of the world